Oral Supplementation of an Alkylglycerol Mix Comprising Different Alkyl Chains Effectively Modulates Multiple Endogenous Plasmalogen Species in Mice - Paul, Sudip (Metabolites, 2021)
Plasmalogens or alkenylphospholipids are a sub-class of glycerophospholipids with numerous biological functions and are thought to have protective effects against metabolic disease. Dietary supplementation with alkylglycerols (AKGs) has been shown to increase endogenous plasmalogen levels, however effective modulation of different molecular plasmalogen species has not yet been demonstrated. In this study, the effects of an orally-administered AKG mix (a mixture of chimyl, batyl and selachyl alcohol at a 1:1:1 ratio) on plasma and tissue lipids, including plasmalogens, was evaluated. Mice on a Western-type diet were treated with either an AKG mix or vehicle (lecithin) for 1, 2, 4, 8 and 12 weeks. Treatment with the AKG mix significantly increased the total plasmalogen content of plasma, liver and adipose tissue as a result of elevations in multiple plasmalogen species with different alkenyl chains. Alkylphospholipids, the endogenous precursors of plasmalogens, showed a rapid and significant increase in plasma, adipose tissue, liver and skeletal muscle. A significant accumulation of alkyl-diacylglycerol and lyso-ether phospholipids was also observed in plasma and tissues. Additionally, the dynamics of plasmalogen-level changes following AKG mix supplementation differed between tissues. These findings indicate that oral supplementation with an AKG mix is capable of upregulating and maintaining stable expression of multiple molecular plasmalogen species in circulation and tissues.